Exploring public health education’s integration of critical race theories: A scoping review - Collins, Sarah L.; Smith, Travis C.; Hack, George; Moorhouse, Michael D. (Frontiers in Public Health, 2023)
Introduction Public health has declared a commitment toward diversity as a whole, with a commitment toward addressing and dismantling racism being at the forefront. Although public health has admirably taken on this mission, and the foundational principles of public health align with social justice and health equity, public health as a discipline is vastly behind other fields in integrating and utilizing critical race theorizations. Of particular concern is the lack of critical race theorization within public health education materials. Public health education serves as a precursor to public health practice and situates topics and competencies that are essential to one’s foundational public health knowledge and skillset, thus the use of strong theoretical groundings is critical in public health education. Objectives Therefore, to explore the current landscape of public health educational research that employs critical race theories, this study sought to conduct a scoping review investigating the current literature of public health pedagogical, instructional, and curricular efforts that utilize race and antiracist theorization principles as a means to administer public health education. More specifically, we sought to investigate how have faculty and instructors published their integration of race theorization in public health curriculum/instruction within the United States since 2011. Results We found 18 examples from peer-reviewed literature of curricular, pedagogical, or instructional practices and strategies that integrate critical theories of race, including contemplative pedagogy (n = 1), antiracism (n = 3), Public Health Critical Race praxis (n = 4), Critical Race (n = 5), critical service-learning/community engagement (n = 2), ethnic studies (n = 1), and intersectionality (n = 2). Conclusion These articles present a wide breadth of innovative approaches to infusing critical race studies within public health higher education, ranging from individual assignments to course design and implementation to institutional culture change, thus demonstrating the multifaceted nature of critical race studies within micro-learning communities and macro-discipline practices. Identifying theoretically grounded, exemplary models and scholarly recommendations of pedagogical, instructional, and curricular practices provides readers the opportunity to borrow from successful practices and implement concepts of race, racism, antiracism, intersectionality, and more into their classrooms.